Mesenchymal stem cells added to second-line therapy improve response and failure-free survival in steroid-refractory acute graft-versus-host disease after allogeneic hematopoietic stem cell transplantation: A meta-analysis of randomized controlled trials - Xiao, Man; Yan, Yinghu; Zhang, Rui; Wang, Dan; Wang, Li; Zhao, Yameng; Yang, Jinhong (Frontiers in Oncology, 2025)
BackgroundSteroid-refractory acute graft-versus-host disease (aGVHD) remains a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT), with limited effective treatment options. Mesenchymal stem cells (MSCs) have emerged as a promising therapeutic approach due to their immunomodulatory and tissue-repair properties. However, inconsistent results existed.MethodsA systematic literature search was conducted in PubMed, Embase, and the Cochrane Central Register of Controlled Trials up to May 2025. Randomized controlled trials (RCTs) evaluating MSCs plus second-line therapy versus second-line therapy alone in patients with steroid-refractory aGVHD were included. Meta-analysis was performed using random-effects models to pool risk ratios (RR) or hazard ratios (HR) with 95% confidence intervals (CIs).ResultsFour RCTs comprising 650 patients were included. MSC administration significantly improved overall response (RR: 1.13, 95% CI: 1.03-1.23, P = 0.007) and complete response rates (RR: 1.43, 95% CI: 1.19-1.70, P < 0.001). Subgroup analysis showed consistent benefits in patients with skin or gut involvement, multiorgan disease, and adults. MSC treatment also reduced the incidence of chronic GVHD (HR: 0.60, 95% CI: 0.42-0.86, P = 0.005) and improved failure-free survival (HR: 0.72, 95% CI: 0.54-0.95, P = 0.022), although no significant overall survival benefit was observed. The safety profile was comparable with controls.ConclusionsThe addition of MSCs to second-line therapy significantly improves treatment response, reduces chronic GVHD incidence, and prolongs failure-free survival in patients with steroid-refractory aGVHD, with a favorable safety profile. These findings support MSC-based therapy as a promising strategy for this high-risk population.